2014
DOI: 10.5586/aa.2014.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of weather on concentrations of airborne Artemisia pollen using circular statistic

Abstract: A b s t r a c tThe diurnal pollen pattern of Artemisia seems to be similar in many regions in Central and Eastern Europe, with its highest concentration before noon. This research is a continuation of a preliminary study that was carried out in Rzeszów 10 years ago. The Spearman nonparametric correlation test and the angular-linear correlation were used to verify assumptions about the influence of meteorological parameters on daily and hourly variations of Artemisia pollen concentrations in the atmosphere. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…e impact of meteorological conditions on daily pollen concentration is very complex as many factors may act differently on airborne pollen level. In general, it has been however shown that an increase in daily air temperature oen correlates positively with higher concentrations of airborne pollen grains in most allergenic taxa (Borycka & Kasprzyk, 2014;Dąbrowska-Zapart et al, 2018;Dąbrowska-Zapart & Niedźwiedź, 2020;Grewling et al, 2019b;Kubik-Komar et al, 2018;Weryszko-Chmielewska et al, 2006). On the other hand, rainfall (recorded during the pollen season) oen decreases pollen concentrations in the air, potentially due to the "washout" effect.…”
Section: Bioaerosols In the Outdoor Airmentioning
confidence: 99%
“…e impact of meteorological conditions on daily pollen concentration is very complex as many factors may act differently on airborne pollen level. In general, it has been however shown that an increase in daily air temperature oen correlates positively with higher concentrations of airborne pollen grains in most allergenic taxa (Borycka & Kasprzyk, 2014;Dąbrowska-Zapart et al, 2018;Dąbrowska-Zapart & Niedźwiedź, 2020;Grewling et al, 2019b;Kubik-Komar et al, 2018;Weryszko-Chmielewska et al, 2006). On the other hand, rainfall (recorded during the pollen season) oen decreases pollen concentrations in the air, potentially due to the "washout" effect.…”
Section: Bioaerosols In the Outdoor Airmentioning
confidence: 99%
“…The effect of wind direction on the clustering pattern was studied by circular statistics (Sadyś et al, 2015, Borycka and Kasprzyk, 2014, Maya-Manzano et al, 2017. The circular average of the prevalent wind direction was calculated for the days associated with each cluster.…”
Section: =1mentioning
confidence: 99%